PENGARUH FORTIFIKASI TEPUNG TULANG IKAN NILA (Oreochromis niloticus) TERHADAP KARAKTERISTIK SENSORIS MIE KERING DAN POTENSINYA SEBAGAI SUMBER KALSIUM: Effect Of Nile Tilapia Bone Flour (Oreochromis niloticus) Fortification On The Sensory Characteristics Of Dried Noodles And Its Potential As A Calcium Source - Izhar Amirul Haq; Hudriyah Masithah; Harist Ramadhan; Tanti Fitriawati (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2026)
This study aimed to analyze the effect of tilapia bone flour (Oreochromis niloticus) fortification on the sensory characteristics of dry noodles and to evaluate its potential as a natural calcium source. The study employed a laboratory experimental method with three fortification treatments of tilapia bone flour, namely 3% (F1), 6% (F2), and 8% (F3). The observed parameters included appearance, aroma, taste, and texture using a 1–5 hedonic scale test involving untrained panelists. Data were analyzed using the Kruskal–Wallis test at a 5% significance level. The results showed that fortification of tilapia bone flour up to 8% concentration did not significantly affect all organoleptic parameters (p>0.05). The highest average scores were obtained in treatment F1 for appearance (3.97), texture (4.03), and taste (3.76), while the highest aroma score was 3.59. The F1 formulation with 3% tilapia bone flour fortification was considered the best treatment based on panelists’ acceptance level. The high calcium content in tilapia bone flour indicates its potential utilization as a functional food fortification ingredient derived from fishery by-products. This study demonstrates that tilapia bone flour has the potential to be used as a natural calcium source without significantly reducing the sensory quality of dry noodles.